2005
DOI: 10.1590/s1519-566x2005000100011
|View full text |Cite
|
Sign up to set email alerts
|

Seleção de isolados de Beauveria bassiana para o controle biológico da broca-do-café, Hypothenemus hampei (Ferrari) (Coleoptera: Scolytidae)

Abstract: -Hypothenemus hampei (Ferrari) (Coffee Berry Borer) is one of the most important coffee pests. Its control is carried out mainly using synthetic chemical products, which contaminate the environment, food and farmers. The entomopathogenic fungus Beauveria bassiana is a natural enemy of coffee berry borer and presents potential for biological control. With the objective to select strains of B. bassiana for the management of H. hampei, the virulence of 61 strains, from diverse hosts and geographic regions, were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
14

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 3 publications
1
12
0
14
Order By: Relevance
“…Inducer substrates have been tested in order to increase the protein content and to release the extracellular proteases to make easier the studies on kinetic activity and structure and to correlate with virulence levels of the fungal strain in bioassays on insects. Neves and Hirose (2005) observed that the Brazilian B. bassiana strain CG432 bioassayed on coffee berry borer, Hypothenemus hampei, presented better conidia production and more than 70% of mortality, with 10 8 conidia/mL concentration among 61 Brazilian strains when reactivated on the same insect. Previous studies showed that extracelullar proteases produced by this strain were active at pH 4.5, 7.0 and 9.5, suggesting the production at least three different type of proteases (Stürmer et al, 2003(Stürmer et al, /2004.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Inducer substrates have been tested in order to increase the protein content and to release the extracellular proteases to make easier the studies on kinetic activity and structure and to correlate with virulence levels of the fungal strain in bioassays on insects. Neves and Hirose (2005) observed that the Brazilian B. bassiana strain CG432 bioassayed on coffee berry borer, Hypothenemus hampei, presented better conidia production and more than 70% of mortality, with 10 8 conidia/mL concentration among 61 Brazilian strains when reactivated on the same insect. Previous studies showed that extracelullar proteases produced by this strain were active at pH 4.5, 7.0 and 9.5, suggesting the production at least three different type of proteases (Stürmer et al, 2003(Stürmer et al, /2004.…”
Section: Introductionmentioning
confidence: 95%
“…Media produced conidia were sprayed on H. hampei alive adults previously treated with 0.5% sodium hypochlorite solution placed on Petri dishes and incubated at 25 o C until insect death. Newly emerged conidia from the insect were subcultured not more than four times, at ten days intervals in solid culture medium and used to prepare the reactivated inoculum suspension containing 10 8 conidia/mL (Neves and Hirose, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A seguir, uma suspensão dos conídios obtida foi utilizada para imergir adultos vivos de brocado-café (Hypothenemus hampei) conforme descrito por Hirose (2005). Após a morte do inseto, os conídios recém-emergidos do inseto morto, "conídios ativados", foram novamente repicados, no máximo três vezes, em meio de cultura sólido.…”
Section: Ativação Do Inóculounclassified
“…B. bassiana cepa CG432 isolada de insetos mortos Hemiptera: Membracidae na região nordeste do Brasil, demonstrou elevado crescimento sobre adultos de broca do café Hypothenemus hampei (Ferrari) HIROSE, 2005), e rápida produção de proteases extracelulares em apenas 2 dias de cultivo inoculado com suspensão de conídios previamente ativados em seu hospedeiro (ITO et al, 2007), sendo este tempo de produção de proteases, muito inferior aos publicados por cultivos de B. Bassiana realizados em meio enriquecidos com substratos protéicos como gelatina e caseína (URTZ; RICE, 2000) ou com cutícula moída de gafanhoto (St LEGER et al, 1986a).…”
unclassified
“…(Alves & Lecuona 1998). Também, Neves & Hirose (2005) atribuíram essas variações na virulência entre os isolados, possivelmente à forma de inoculação, à concentração da suspensão de conídios, e à variabilidade natural entre os isolados.…”
Section: Virulência De Isolados De M Anisopliae E B Bassiana Para Lunclassified